2023
DOI: 10.34133/research.0107
|View full text |Cite
|
Sign up to set email alerts
|

Health and Disease:Akkermansia muciniphila, the Shining Star of the Gut Flora

Abstract: Akkermansia muciniphila ( A. muciniphila ) has drawn much attention as an important gut microbe strain in recent years. A. muciniphila can influence the occurrence and development of diseases of the endocrine, nervous, digestive, musculoskeletal, and respiratory systems and other diseases. It can also improve immunotherapy for some cancers. A. muciniphila is expected to become a new probiotic in addition to Lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 228 publications
0
8
0
Order By: Relevance
“…We did observe that Akkermansia muciniphila was differentially increased in all these disorders (PD, schizophrenia, and T2D) as well (Figure 3e). This finding is highly controversial in the literature, since previous studies have observed that Akkermansia muciniphila is both beneficial (53) and pathogenic (54). From our analysis, it is difficult to determine the causal role of Akkermansia muciniphila in these diseases.…”
Section: Resultsmentioning
confidence: 97%
“…We did observe that Akkermansia muciniphila was differentially increased in all these disorders (PD, schizophrenia, and T2D) as well (Figure 3e). This finding is highly controversial in the literature, since previous studies have observed that Akkermansia muciniphila is both beneficial (53) and pathogenic (54). From our analysis, it is difficult to determine the causal role of Akkermansia muciniphila in these diseases.…”
Section: Resultsmentioning
confidence: 97%
“…There were five genera related to bone metabolism between the DIO and CON groups, and the observed changes in g__Akkermansia abundance were unique in the DIO. In the gut microbiota, Akkermansia (Phylum Verrucomicrobia) influences the onset and progression of several diseases [ 49 ] and maintains intestinal barrier homeostasis [ 50 ]. The loss of Akkermansia impairs intestinal integrity, increases intestinal leakage, and, by extension, promotes metabolic endotoxemia, inflammation, and insulin resistance [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WoSCC, recognized for its extensive interdisciplinary scope, hosts over 170 million articles from more than 250 academic disciplines (Shi et al, 2022). Specifically, the database hosts a significant volume of literature pertinent to our study, with a considerable number of articles and cited references directly related to gut microbiota research within the realm of endocrinology and metabolism (Zhang et al, 2022;Li C. et al, 2023;Xue et al, 2023;Takeuchi et al, 2023). Given the database's extensive usage and acclaim in scientometric research, it provides a solid basis for analyzing the trajectory of gut microbiota research in our field.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, specific bacterial species such as Akkermansia muciniphila have been identified for their distinctive roles in modulating metabolic pathways, thereby presenting potential targets for therapeutic intervention. This bacterium, residing in the mucus layer, enhances the thickness and integrity of the mucosal layer and contributes to the prevention of inflammation caused by disturbances in gut permeability (Xue et al, 2023). Furthermore, studies have linked the presence of Akkermansia muciniphila with favorable impacts on glucose metabolism, suggesting a negative correlation with markers of insulin resistance and obesity, thereby offering potential therapeutic avenues for metabolic disorders (Shi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%